FRI0232 PATIENT PERCEPTION OF SLE BURDEN: THE ROLE OF ORGAN DAMAGE. (June 2019) - Elefante, Elena; Tani, Chiara; Ferro, Francesco; Stagnaro, Chiara; Parma, Alice; Carli, Linda; Signorini, Viola; Mosca, Marta
Abstract : Background: physician-based assessment of Systemic Lupus Erythematosus (SLE) may not be able to capture the real disease impact on patients' life. In the literature, the impact of disease damage on patients' quality of life (QoL) is controversial. Objectives: Objective of our study was to investigate the role of organ damage in determining patient perception of SLE burden. Methods: this is a cross-sectional study that enrolls patients with a diagnosis of SLE (ACR 1997 criteria). For each patient, demographics, comorbidities, treatment, clinical and laboratory data were collected. Disease damage was evaluated with the SLICC-Damage Index (SDI) and a score >2 was defined as "severe damage". The BILD (Brief Index of Lupus Damage) was used for patient self-evaluation of organ damage. Finally, the Lupus Impact Tracker (LIT) questionnaire was used to assess patient perception of SLE burden. Results: we included 246 adult SLE patients (94.7% Caucasian, 93.1% female, mean age 45.31±13.2 years, mean disease duration 14.3±9.8 years). As for cumulative organ involvement in our cohort, the most prevalent was articular involvement (67.5%), followed by cutaneous (54.1%), hematological (51.2%), renal (43.9%) and serositis (17.9%); 11.8% had a history of NPSLE. Among comorbidities, 10.9% of patients had a concomitant fibromyalgia. 48.8% of patients was presenting at least one organ damage; among those patients, the median SDI was 2 (IQR 1-3); 16.3% of patients had a "severe damage" and among them median SDI was 4 (IQR 3-6). The most frequent items of organ damage in our cohort were: cataract (19.9%), deforming or erosive arthritis (10.2%) and osteoporosis with fracture (8.5%). Moreover, a significant number of patients (18.3%) met the criteria for neuropsychiatric damage, mainly cerebrovascular accidents (7.3%), seizures (5.3%) and cognitive impairment (4.1%). Finally, a not negligible number of patients had premature gonadal failure (4.5%) and malignancy (6.5%). As far as patients' perception is concerned, the median LIT score in the cohort was 22, 5 (IQR 7.5-40) and median BILD was 1 (IQR 0-2). In a multiple linear regression analysis, we found a direct positive correlation between the SDI score and age at enrollment and disease duration (p<0, 001). Severe damage resulted associated with a history of serositis (p<0, 01) and NPSLE (p<0, 001). We also found a positive linear correlation between the SDI score and the patient's self- reported damage (BILD score; p<0, 001) and with the patient's perception of disease burden (LIT; p<0, 01), irrespective of age and disease duration. In particular, in the multivariate analysis, higher SDI scores were significantly associated with a poorer perception of disease burden in terms of: future planning (p<0, 001), usual activities, family responsibilities, discomfort due to physical appearance (p<0, 01) and drug side effects (p<0, 05), irrespective of fibromyalgia and age at enrollment. Among the different types of organ damage, we found that cognitive impairment, cerebrovascular accidents and premature gonadal failure mainly contribute to determine SLE burden. In fact, they were significantly associated with higher LIT scores (p<0, 05). Conversely, SDI score was not related with health-related quality of life and fatigue as measured by SF-36 and FACIT respectively, neither with fibromyalgia. Conclusion: disease damage seems to have a role in determining patient perception of SLE burden, mainly affecting patients' ability to plan the future and to fulfill daily activities and family responsibilities. In particular, neuropsychiatric damage exerts the greatest influence on patient perception of SLE impact. References: [1] Yazdany J. et al, Arthritis Care Res (Hoboken). 2011 Aug;63(8):1170-7 Disclosure of Interests: Elena Elefante: None declared, Chiara Tani: None declared, Francesco Ferro: None declared, Chiara Stagnaro: None declared, Alice Parma: None declared, Linda Carli: None declared, Viola Signorini: None declared, Marta Mosca Paid instructor for: GlaxoSmithKline, Lilly, UCB